Cities on the Move : A World Bank Urban Transport Strategy Review - World Bank (Washington, DC, 2013)
The report's objectives are i) to better understand the nature and magnitude of urban transport problems, particularly in respect of the poor, and ii) to articulate a strategy by which the World Bank and other agencies can assist national and city governments to address these problems. The first part of the report considers how urban transport can be used as an instrument of urban development and poverty reduction. Chapter 2 discusses how transport reduces poverty. Chapter 3 examines how urban transport policies can be focused more specifically on meeting the needs of the poor but touches on other transport related aspects of the quality of life of poor people. Chapter 4 considers the urban environment, focusing on air pollution to which the poor are particularly vulnerable, while Chapter 5 considers problems of personal safety and security. The second part of the report considers how the objectives can be pursued by using a range of instruments. Chapter 6 considers the provision and management of road infrastructure. Chapter 7 discusses road based public transport, including the role of the informal sector. Chapter 8 considers the role and limitations of mass transit. Chapter 9 pays special attention to non-motorized transport. Chapter 10 raises the issues of pricing and financing, and Chapter 11, looks at institutional arrangements. Finally, Chapter 12 discusses the implications for the instruments and lending strategies of the Bank.